Air bubbles in fibrous caseinate gels investigated by neutron refraction, X-ray tomography and refractive microscope. (October 2018) - Tian, Bei; Wang, Zhaojun; van der Goot, Atze Jan; Bouwman, Wim G.
Abstract: Fibrous protein gels have the potential to form the basis for the next-generation of meat analogue. It is suggested that fibre anisotropy is related to air bubbles present in the gel. Given the complexity and heterogeneity of the samples, several quantitative techniques are needed to ensure a comprehensive understanding of the air bubbles. We performed neutron refraction experiments to study the size and shape of the air bubbles in three calcium caseinate samples containing different H2 O to D2 O ratios. Refractive microscopy and X-ray tomography (XRT) analysis were done on the same samples to provide complementary information. The deformation degree and average width of the air bubbles were obtained from both the XRT and neutron refraction experiment. A neutron refraction model calculates the average area and volume of a single air bubble, which correspond to the largest area and volume fractions of all the air bubbles from the XRT analysis. Additionally, we found that the H2 O to D2 O ratios in the sample largely influence the size, number distribution and deformation degree of the air bubbles. The neutron refraction technique can be a simple and complementary method to help understanding the role of air bubbles in the meat analogue. Graphical abstract: Image 1 Highlights: A model is proposed to describe the neutron refracted by the air bubbles in a fibrous calcium caseinate gel. Air bubbles are larger and more elongated in gels with higher D2 O to H2 O ratios. Neutron refraction technique can be a suitable tool to study the dispersed phase in composite food materials.